Flexible Microstrip Antenna for Iot and 5g Wireless Systems - Kaschel-Carcamo, H; Cordero-Leiva, S (Institute of Electrical and Electronics Engineers Inc., 2022)
The proposed antenna is flexible, and portable for wireless systems. The textile antenna is useful for various applications, such as 5G, IoT, and WBAN. To meet the portable antenna requirements, properties such as flexibility, cost, and data rate must be taken into account. The article details the design, simulation, and fabrication of a rectangular antenna by using an electromagnetic simulator (CST), as well as analyzing its performance with a flexible substrate. The antenna is designed with a flexible textile substrate material for a frequency of 3.5 GHz. Parameters, such as reflection coefficient, trajectory loss, gain, and antenna cost in the human model are analyzed as well, in addition to the specific absorption rate of the antenna in the human body so that it is within international standards. © 2022 IEEE.
Keywords: 5G; Flexible Antenna; IoT; SAR; Textil antenna; WBAN